Factors affecting the acceptance of financial technology among asnaf for the distribution of zakat in Selangor: a study using UTAUT - Yahaya, Muhamad Hasif; Khaliq, Ahmad (IIUM Institute of Islamic Banking and Finance (IIiBF), International Islamic University Malaysia (IIUM), 2019)
Financial technology or fintech, which is technology-based financial services has become a major role player in enhancing the effectiveness and efficiency of financial services. The financial industry has evolved significantly globally with the impact of technological innovation. For example in Malaysia, the financial institution can offer various services to their customers in facilitating and fulfilling their financial needs. Furthermore, the impact of fintech also had changed the social finance sector such as Zakat Institutions. For example, in Malaysia during the old days people have to go to the counter to pay zakat or to collect the zakat as well. Nevertheless with the help of various technology-based financial services such as online banking, mobile banking and others that are provided by the financial institution, the collection of zakat has been empowered. Contrary to that, in terms of the distribution aspect there are still a lot that can be improved with the help of fintech. Thus, in this study mobile banking will be the focus in improving zakat distribution rate. This study aims to explore factors that could influence asnaf acceptance rate in adopting mobile banking for the distribution of zakat using the UTAUT model. This study consists of empirical data collected from the state of Selangor, Malaysia.